2022
DOI: 10.1021/acs.jpcb.2c06372
|View full text |Cite
|
Sign up to set email alerts
|

Understanding X-ray Photoelectron Spectra of Ionic Liquids: Experiments and Simulations of 1-Butyl-3-methylimidazolium Thiocyanate

Abstract: We demonstrate a combined experimental and computational approach to probe the electronic structure and atomic environment of an ionic liquid, based on core level binding energies. The 1-butyl-3-methylimidazolium thiocyanate [C4C1Im][SCN] ionic liquid was studied using ab initio molecular dynamics, and results were compared against previously published and new experimental X-ray photoelectron spectroscopy (XPS) data. The long-held assumption that initial-state effects in XPS dominate the measured binding energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Our first example is an ion-pair dimer, 1-butyl-3-methylimidazolium (C 4 C 1 Im + ) with a thiocyanate (SCN – ) counter-ion, representing a typical dialkylimidazolium ionic liquid . This and other room-temperature ionic liquids have been studied using NEXAFS spectroscopy at the nitrogen and sulfur K-edges .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first example is an ion-pair dimer, 1-butyl-3-methylimidazolium (C 4 C 1 Im + ) with a thiocyanate (SCN – ) counter-ion, representing a typical dialkylimidazolium ionic liquid . This and other room-temperature ionic liquids have been studied using NEXAFS spectroscopy at the nitrogen and sulfur K-edges .…”
Section: Resultsmentioning
confidence: 99%
“…Our first example is an ion-pair dimer, 1-butyl-3-methylimidazolium (C 4 C 1 Im + ) with a thiocyanate (SCN − ) counter-ion, representing a typical dialkylimidazolium ionic liquid. 124 This and other room-temperature ionic liquids have been studied using NEXAFS spectroscopy at the nitrogen and sulfur K-edges. 125 In accompanying calculations, it was observed that excited states could be delocalized across the ion pair in some cases, 125 such that computational modeling should not be limited to either the cation or the anion.…”
Section: A Comparison Of Tdks To Lr-tddftmentioning
confidence: 99%
“…can also be used as a secondary measure of the anion-dependent interaction strength ( Figure 2 b), although E B (N cation 1s,exp.) is usually used, as C anion 1s peaks can overlap with C hetero 1s and C 2 1s peaks, e.g., for [SCN] − -based ILs, 66 making fitting more challenging when obtaining E B (C hetero 1s,exp.) and E B (C 2 1s,exp.)…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion was based on the fact that initial-state calculations gave excellent visual matches for the N 1s and final-state calculations for S 2p and N 1s in the anion [SCN] − gave the same trends as initial-state calculations. 66 However, no results were presented on anion-dependent interactions. Hence, whether the XPS-derived anion-dependent interaction strength scale is due to initial-state effects or final-state effects is still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Our first example is an ion-pair dimer, 1-butyl-3-methylimidazolium (C 4 C 1 Im + ) and thiocyanate (SCN − ), representing a typical dialkylimidazolium ionic liquid. 94 This and other roomtemperature ionic liquids have been using NEXAFS spectroscopy at the nitrogen and sulfur K-edges. 95 In ac- The complete TDKS spectrum ("full") is compared to filtered spectra involving only the O(1s), N(1s), or S(2p) orbitals, as indicated.…”
Section: B Continuum Artifacts Figurementioning
confidence: 99%